2019
DOI: 10.1016/j.psychres.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized trial of a dual n-back emotional working memory training program for veterans with elevated PTSD symptoms

Abstract: Anxiety is characterized by excessive attention to threatening information, leading to impaired working memory (WM) performance and elevated anxious thoughts. Preliminary research indicates that individuals with PTSD show particular difficulty with WM in emotional contexts (Schweizer et al., 2011). Although several studies show that computerized training can improve WM capacity for anxious individuals (Owens et al., 2013; Schweizer et al., 2011 & 2013), there has been very little research on WM training for PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
(37 reference statements)
1
31
1
Order By: Relevance
“…We all know that the onset of migraine and epilepsy is closely related to mood [15][16][17] . During COVID-19 outbreak, children were restricted in home, their patients would ask them to take some measures to prevent infection, and they also heard a good deal of disaster-related information, which brought anxiety and panic to them 18 .Thus we supposed that the increasing of these diseases was associated with the emotional instability caused by COVID-19. Studies also proposed that epilepsy patients showed signi cantly higher 6-item Kessler Psychological Distress Scale scores than healthy controls, suffering from psychological distress, in turn, can induce seizure attack 19 .…”
Section: Change Of Disease Distribution During Covid-19 Outbreakmentioning
confidence: 99%
“…We all know that the onset of migraine and epilepsy is closely related to mood [15][16][17] . During COVID-19 outbreak, children were restricted in home, their patients would ask them to take some measures to prevent infection, and they also heard a good deal of disaster-related information, which brought anxiety and panic to them 18 .Thus we supposed that the increasing of these diseases was associated with the emotional instability caused by COVID-19. Studies also proposed that epilepsy patients showed signi cantly higher 6-item Kessler Psychological Distress Scale scores than healthy controls, suffering from psychological distress, in turn, can induce seizure attack 19 .…”
Section: Change Of Disease Distribution During Covid-19 Outbreakmentioning
confidence: 99%
“…Following randomization, the tDCS apparatus was attached, and participants completed 60 min of WMT. This training period was approximately two to three times the regular dose of one WMT session typically used in the literature (Larsen et al, 2019;Schweizer et al, 2013). Participants in the tWMT condition received 30 min of current stimulation while training WM processes, and participants in the sWMT only received 30 s of stimulation (ramp-up) to induce the feeling of stimulation (i.e., tingling).…”
Section: Study Proceduresmentioning
confidence: 99%
“…WM was trained with an emotionally adaptive dual nback task. This WMT involved a presentation of emotionally salient faces and words to target constant updating of information in WM and shifting between two different modes of stimuli (Larsen et al, 2019). In each trial, one of eight fearful faces (4 males and 4 females) was presented within a 3×3 grid while a negative spoken word (female voice; disaster, cancer, etc.)…”
Section: Computerized Working Memory Trainingmentioning
confidence: 99%
See 2 more Smart Citations